Application Of Pull-Kanban System To Reduce Inventory And Lead Time In A Manufacturing System - Hwang, Jia Qi (Universiti Sains Malaysia, 2017)
This thesis focused on manufacturing lead time and inventory cost reduction in medium mix low volume production with Pull system or Kanban system. The production is a fixed position machine manual assembly line. The initial condition of the production such as the manufacturing lead time and process lead time was collected from time study and the data was analyzed. The submodule assembly processes were given attention as they consume raw material. Inventory level was collected in terms of cost from the ERP software of the company. In design stage, a mixed pull system which consisted of Kanban system and sequential pull system was designed. The submodules were evaluated based on some criteria such as customization level, size, lead time and whether they can be assembled externally and then were decided by using simulation and Design of Experiment (DoE). The quantity of Kanban was calculated and decided by using qualitative or quantitative approach and Taguchi method as well. The work procedure, information and material transfer steps were designed according to the available human resource and their skill. The result after Kanban implementation showed 45.97% lead time reduction from 33.72 days to 20.17 days and 28.49% inventory cost reduction from RM 132857.14 to RM 9500.00. After the termination stage stabilized, a Standard Operating Procedure(SOP) was prepared to maintain the improvement made.